PENERAPAN SISTEM OUTSORCING DAN HAK-HAK SOSIAL EKONOMI TENAGA KERJA PT. INDOSAT OOREDOO (STUDI KASUS DI SALES AREA SERANG) - Gian Sumarna Gian Sumarna (NIAGARA Scientific Journal, 2018)
The formulation in this research is "How to Implement the Outsourcing System and Socio-Economic Rights of Labor PT. Indosat Ooredoo (Case Study in Sales Area Attack) ? The method used is descriptive method. This research is done at PT. Indosat Ooredoo Sales Area Serang. While the informants consisted of all Partner Employees and Organic Employees of PT. Indosar Ooredoo Serang Sales Area, Service Banten Province Manpower and Transmigration, Banten Province Social Service and Members DPRD Banten Province. The results of the research concluded that, Implementation of the Outsourcing System and Rights Socio-Economic Labor of PT. Indosat Ooredoo (Case Study in Serang Sales Area) not yet running effectively, this is seen from various aspects: Aims and objectives outsourcing implementation guidelines, implementation measures for implementation guidelines outsourcing, resources relevant to the implementation of the outsourcing implementation, Departments/Agencies related to the implementation of outsourcing, outreach efforts and consistency, outsourcing implementation refers to statutory regulations, socio-economic rights of outsourced workers, supervision and training, mechanisms communication/coordination between agencies/agencies/entrepreneurs/SP/labor, influence economic, social and political environment towards the implementation of outsourcing